KONFLIK ISLAM DAN ISRAEL DI PALESTIN: TENTANGAN, ISU DAN PENYELESAIANNYA DALAM KARYA AL-FARUQI(ISLAM AND ISRAEL CONFLICT IN PALESTINS: CONFRANTATION, ISSUE AND SOLUTION IN THE AL-FARUQI WORK) (UMRAN - Journal of Islamic and Civilizational Studies, 2015)
This paper discusses the views of al-Faruqi on the issue of Israel-Palestine as critically presented in his work Islam and the Problem of Israel. It aims to analyze his perspective on the significant impact of Israel’s occupation in the Gaza’s strip, explaining in detail some historical issues and suggesting solution to the conflict. The research attempts to investigate his stand concerning the Israel-Palestine war, the way he analyzes the issue and its comparison with other works of similar orientation. The research is based on descriptive, analytical and comparative method, by describing in depth al-Faruqi’s work and its significance in addressing the plight and catastrophic consequence of war, and its comparison with other works produced on this theme. The research findings and its conclusions are important to test the ideas propounded by al-Faruqi to effectively end the conflict in the West Bank.
Keywords: al-Faruqi; Islam and the Problem of Israel; Israel-Palestine conflict; development of conflict; Middle East; Zionism